Analysis of Load Flow Method With Static Var Compensator (SVC) for Minimizing Transmission Losses in Power System : A Case Study of 500 KV Java-Bali Electrical Power System - Chico Hermanu Brillianto Apribowo; Oktavian Listiyanto (Universitas Sebelas Maret (UNS), 2019)
Demand for electricity is increasing rapidly, the consequence of this is a threat to the stability of the electrical system, one of which is the voltage stability. FACTS or Flexible Alternating Current Transmission System is electronic equipment that is able to regulate electric power transmission that can be used to overcome stability problems. This research will analyze the use of Static Var Compensator (SVC) as one of the equipment from FACTS to overcome the stability of the most critical buses by using the 500 kV Java-Bali electricity system using PSAT. Results from using the power flow method in the 500 kV Java-Bali case show that the total active power generation is 12.144 p.u. and the total reactive power generation is 5.268 p.u. This value is obtained from the total addition of active power generation and reactive power of all plants in the 500 kV Java-Bali system. While the total active power load is worth 12.058 p.u. and the total reactive power load is 4.65 p.u. This value is obtained from the total load on each bus plus the total losses incurred on the line.